1997
DOI: 10.1093/ajcn/66.4.803
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and cognitive function in a group of elderly people

Abstract: Associations between dietary intake and cognitive performance were examined in 260 elderly people aged 65-90 y who were free of significant cognitive impairment. Dietary intake was monitored with a weighed-food record for 7 consecutive days. The subjects' cognitive capacity was tested by using Folstein et al's Mini-Mental State Examination (MMSE) and Pfeiffer's Mental Status Questionnaire (PMSQ). Subjects with adequate MMSE results (> or = 28 points) had lower intakes of monounsaturated fatty acids, saturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
207
1
5

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 314 publications
(236 citation statements)
references
References 22 publications
23
207
1
5
Order By: Relevance
“…The vitamins that play a substantial role in the immunity of the elderly include vitamins A, C, D, E and B6; the minerals affecting immune function include zinc and iron (Kelley & Bendich, 1996;Bell & High, 1997). Suggestive rather than conclusive studies have indicated an association between cognitive function impairment in the elderly and a deficient intake of micronutrients, especially folate, vitamins C and E, b-carotene, zinc and iron (Warsama et al, 1996;Ortega et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The vitamins that play a substantial role in the immunity of the elderly include vitamins A, C, D, E and B6; the minerals affecting immune function include zinc and iron (Kelley & Bendich, 1996;Bell & High, 1997). Suggestive rather than conclusive studies have indicated an association between cognitive function impairment in the elderly and a deficient intake of micronutrients, especially folate, vitamins C and E, b-carotene, zinc and iron (Warsama et al, 1996;Ortega et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Zinc deficiency has been implicated as a possible contributing factor to cognitive decline and neurodegeneration in older adults (Cuajungco & Faget, 2003). Ortega et al (1997) investigated the effects of diet on cognitive functioning in 260 participants aged 65-90 y whose dietary intake was recorded for 7 days. They found higher cognitive functioning, as measured by the Mini Mental State Examination (MMSE; Folstein et al, 1975) and Pfeiffer's Mental Status Questionnaire (PMSQ;Pfeiffer, 1975), with better nutritional diets.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive decline in the elderly can be caused or worsened by nutritional deficiencies (Ortega et al , 1997;Greenwood & Winocur, 1999). Some group B vitamins, such as folic acid, cyanocobalamine and pyridoxine are essential for correct brain function; inadequate status in these nutrients has been associated with loss of cognitive function (Ortega et al, 1996;Selhub et al, 2000).…”
Section: Introductionmentioning
confidence: 99%